2023
DOI: 10.1002/cb.2208
|View full text |Cite
|
Sign up to set email alerts
|

The role of dark pattern stimuli and personality in online impulse shopping: An application of S‐O‐R theory

Abstract: Online impulse shopping is a growing industry. This paper uses the Stimulus‐Organism‐Response framework to model online impulse purchase behavior using a novel combination of stimuli and organism characteristics. The stimuli: social proof, limited‐quantity scarcity, and high‐demand, are three commonly used website features known as dark patterns. The organism characteristic personality is measured by the big 5 personality traits and persona generated through latent profile analysis. Using the machine learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…The authors demonstrated that dark patterns have a detrimental impact on customer purchase intentions, which is moderated by a reduced fairness perception. Abbott et al (2023) studied dark patterns with respect to online impulse shopping and reported that susceptibility to dark patterns while shopping online is influenced by the big-5 personality traits and persona. Additionally, the authors highlighted that there is a need for tailored interventions to minimize consumer vulnerabilities because of dark patterns.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…The authors demonstrated that dark patterns have a detrimental impact on customer purchase intentions, which is moderated by a reduced fairness perception. Abbott et al (2023) studied dark patterns with respect to online impulse shopping and reported that susceptibility to dark patterns while shopping online is influenced by the big-5 personality traits and persona. Additionally, the authors highlighted that there is a need for tailored interventions to minimize consumer vulnerabilities because of dark patterns.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%